Improved Production of Recombinant Myrosinase in Pichia pastoris - Zuzana Rosenbergová (MDPI AG, 2021)
The effect of the deletion of a 57 bp native signal sequence, which transports the nascent protein through the endoplasmic reticulum membrane in plants, on improved AtTGG1 plant myrosinase production in Pichia pastoris was studied. Myrosinase was extracellularly produced in a 3-liter laboratory fermenter using α-mating factor as the secretion signal. After the deletion of the native signal sequence, both the specific productivity (164.8 U/L/h) and volumetric activity (27 U/mL) increased more than 40-fold compared to the expression of myrosinase containing its native signal sequence in combination with α-mating factor. The deletion of the native signal sequence resulted in slight changes in myrosinase properties: the optimum pH shifted from 6.5 to 7.0 and the maximal activating concentration of ascorbic acid increased from 1 mM to 1.5 mM. Kinetic parameters toward sinigrin were determined: 0.249 mM (Km) and 435.7 U/mg (Vmax). These results could be applied to the expression of other plant enzymes.